2021
DOI: 10.5897/jphe2020.1272
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, knowledge of health effect and attitude towards smoking among undergraduates in a Nigerian University

Abstract: Smoking prevalence has been on the rise among university students in Nigeria despite the high awareness of harmful effects of smoking on health irrespective of the substance smoked, leading to death of millions annually. The aim of this study is to determine the prevalence, knowledge of health effect and attitude towards smoking among students of Alex Ekwueme Federal University Ndufu Alike, Ebonyi State. This was a cross-sectional descriptive study conducted at Alex Ekwueme Federal University Ndufu-Alike Ebony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Doumas et al (22) also confirmed the usefulness of web-based interventions regarding reducing positive attitudes toward alcohol consumption. On the other hand, the evidence indicates that increasing the negative attitude towards substance abuse can be an effective strategy in preventing and reducing substance abuse (23,24). Positive and negative beliefs about smoking can be promoted in programs to reduce smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Doumas et al (22) also confirmed the usefulness of web-based interventions regarding reducing positive attitudes toward alcohol consumption. On the other hand, the evidence indicates that increasing the negative attitude towards substance abuse can be an effective strategy in preventing and reducing substance abuse (23,24). Positive and negative beliefs about smoking can be promoted in programs to reduce smoking.…”
Section: Discussionmentioning
confidence: 99%